Kepemimpinan dan Pelatihan PBB untuk Meningkatkan Kinerja Organisasi Kemahasiswaan di Poltekkes Kebidanan Magelang - Agung Prapsetyo; Darmoko; Kiki Lestari (JURNAL NAGARA BHAKTI, 2026)
Leadership development in student organizations is a strategic investment for Indonesia's future human resources. This community service activity was conducted at Poltekkes Kemenkes Semarang Campus V Kebidanan Magelang, targeting 45 administrators of DEMA and HIMA. The method combines transformational leadership education with Basic Military Training (PBB) drills to strengthen discipline and organizational performance. The activity was executed through theoretical lectures, interactive discussions, and practical marching exercises in the campus field. Results demonstrate significant improvement in participants' understanding of adaptive leadership concepts, basic PBB movements, and the critical role of discipline in achieving collective goals. Participants exhibited high enthusiasm and active engagement throughout all sessions. This initiative establishes a collaborative framework between the Military Academy and health education institutions in cultivating student leaders with strong character, discipline, and nationalism spirit. The program serves as a replicable model for leadership development in vocational education settings across Indonesia.